“Bihari” Identity in Bangladesh: Unraveling the Diasporic Dynamics - Sultana, Tanima (Journal of Integrative and Innovative Humanities, 2025)
The term diaspora is etymologically ambiguous. If on the one hand it is burdened with dispersal, on the other hand it stimulates new possibilities of settlement. People known as diaspora are usually people who have dispersed away from their homeland and, under the tension of not being able to fully assimilate themselves into the existing settlement, attempt to reproduce a new social and cultural formation with a distinct identity tied to their origin or homeland. The Urdu-speaking diaspora living in Bangladesh was born from the dreadful experiences of partition refugees in colonial India like sectarian riots and bloodshed spread in various Indian states like Bihar, Uttar Pradesh, and Punjab since 1946. But they are generally referred to as “Bihari.” The “Bihari” diaspora was identified as “Muhajir” prior to 1971, and subsequently as “stranded-Pakistanis,” “stranded non-Bengalis,” “non-Bengalis,” “Biharis,” “non-locals,” “non-vernacular,” etc. As a diaspora, the “Biharis” have been subjected to multiple travails, both through dispersal and re-settlement. The “becoming” and “being” of these people are determined by the ongoing interplay of history, culture, and power. In this context, this anthropological study has been conducted to unveil the nature of the diasporic dynamics surrounding the identity of the “Bihari” community living in Bangladesh, because this is currently underrepresented in studies of “Bihari” individuals. This paper conceptualizes the diasporic identity of this “Bihari” people, traces its diasporic dynamics by exploring the internal sects and diverse social strata of the people, and explores trajectories of inferiority to deny their diasporic identity.